The Problem of Necessary and Sufficient Conditions and Conceptual Analysis. (October 2015) - Shaffer, Michael J.
Abstract: In this article the standard philosophical method involving intuition‐driven conceptual analysis is challenged in a new way. This orthodox approach to philosophy takes analysanda to be the specifications of the content of concepts in the form of sets of necessary and sufficient conditions. Here it is argued that there is no adequate account of what necessary and sufficient conditions are. So, the targets of applications of the standard philosophical method so understood are not sufficiently well understood for this method to be dependable.